2022
DOI: 10.1007/s00432-022-03993-4
|View full text |Cite
|
Sign up to set email alerts
|

Blimp-1 is a prognostic indicator for progression of cervical intraepithelial neoplasia grade 2

Abstract: Background Progression of cervical intraepithelial neoplasia (CIN) to higher grade disease is associated with persistent human papillomavirus (HPV) infection and an absence of immune-mediated regression. However, the immune microenvironment that distinguishes progression from persistent or regressing lesions has not been well defined. Methods A total of 69 patients under the age of 25 with high-risk HPV-positive cytology and biopsy-confirmed p16-positive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In HPV16/18 lesions, CD4+FoxP3+ cells were strongly correlated with HMGB1, whereas they were strongly correlated with Blimp1 expression in HPV ‘other’ lesions. Previously, we did not find any association between CD4+FoxP3+ cells and disease progression in CIN2+ lesions but did detect an increase in CD4-FoxP3+ cells in lesions that subsequently progressed to higher-grade disease [ 15 ]. Furthermore, we found that Blimp1 and HMGB1 expression in the lesion was associated with a higher likelihood of disease progression.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In HPV16/18 lesions, CD4+FoxP3+ cells were strongly correlated with HMGB1, whereas they were strongly correlated with Blimp1 expression in HPV ‘other’ lesions. Previously, we did not find any association between CD4+FoxP3+ cells and disease progression in CIN2+ lesions but did detect an increase in CD4-FoxP3+ cells in lesions that subsequently progressed to higher-grade disease [ 15 ]. Furthermore, we found that Blimp1 and HMGB1 expression in the lesion was associated with a higher likelihood of disease progression.…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with these observations, commonly reported high-grade cervical disease associated cellular changes when compared with normal tissue include decreased CD4 and CD8 cells and increased IDO1-positive cells [ 34 ]. Changes associated with subsequent disease progression from CIN2 to CIN3 include decreased CD4+, T bet-positive, CD8+, and CD11c+ cells [ 15 ]. Overall, the reduced numbers of T cells in HPV16/18 compared with hr HPV ‘other’ tissues in this study may reflect inhibition of T cell proliferation in the local tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPV genotype was determined using a PCR-based test (Genosearch-31; MBL, Nagoya, Japan) [16]. This test can detect 13 HR HPV types (16,18,31,33,35,39, 45, 51, 52, 56, 58, 59, and 68), probable high-risk (pHR) types (26, 53, 66, 70, 73, and 82), and low-risk (LR) types (6,11,42,44, 54, 55, 61, 62, 71, 84, 89, and 90). To identify additional pHR-HPV types, such as HPV34, 67, and 69, the uniplex PCR method [17] was used for some CIN or VaIN cases that tested negative with the aforementioned test.…”
Section: Pathological Diagnosis Hpv Testing and Confirmation Of Disea...mentioning
confidence: 99%